Exercise intervention for the treatment of trismus in head and neck cancer – a prospective two-year follow-up study. (2nd June 2016) - Pauli, Nina; Svensson, Ulrika; Karlsson, Therese; Finizia, Caterina
Abstract: Background This study aims to investigate the long-term effects of structured trismus intervention in patients with head and neck cancer (HNC) and trismus in terms of mouth opening, trismus-related symptoms and health-related quality of life (HRQL). Material and methods Fifty patients with HNC to receive radiotherapy ± chemotherapy were included in this prospective study along with a matched control group. The intervention group received a 10-week structured exercise with a jaw mobilizing device (TheraBite® jaw device or Engström device). Patients were assessed before and after trismus exercise intervention and at a two-year follow-up. Primary endpoint was maximum interincisal opening (MIO) and secondary endpoints included trismus-related symptoms and HRQL assessed with patient-reported outcome (PRO)-instruments [Gothenburg Trismus Questionnaire (GTQ), European Organization for Research and Treatment of Cancer Core Questionnaire (EORTC QLQ-C30) and the related HNC-specific module the EORTC Head & Neck Questionnaire (EORTC QLQ-H&N35)]. Results The intervention group had a higher MIO at the two-year follow-up compared to the control group (40.5 mm and 34.3 mm, respectively), which was statistically significant. The intervention group also reported less jaw-related problems according to the GTQ and higher functioning as measured by EORTC QLQ-C30 and QLQ-H&N35 compared to the control group. Conclusion A positive persistent effect of exercise intervention for trismus in HNC patients was found with regard to MIO, trismus-related symptoms and HRQL. Exercise intervention is important in long-term treatment of radiation-induced trismus in HNC patients. The trismus-specific questionnaire, GTQ, is a valuable tool for observing and evaluating trismus over time.